Infill development in rural areas between planning ideals and stakeholder interests: The influence of social aspects - Gerend, Jennifer; Beck, Marina (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
The perspectives of municipal representatives and property owners in three rural communities in Bavaria are the subject of this paper on property and infill development. The results of a survey were assigned to four spatially coded settlement types: historic town centres, post-World-War II settlement types, settlements from the 1980s and 1990s, and new developments after 2000. There were considerable differences between these settlement types in many of the responses: The responses from the newer settlements showed a more individualistic attitude than the respondents in the town centres. For example, vacant lots between buildings are often reserved as plots for grandchildren, others serve as green spaces. Little interest in selling is reported. This paper therefore recommends providing tailored support and incentives that take into account the social aspects of land ownership (including long-term lease options, land swaps, or swaps for units in a new building on the site). The results also show that many vacant lots are perceived in the neighbourhood as welcome green spaces. Therefore, administrations should focus more on planning green spaces in small rural communities and re-evaluating existing properties as potential public green spaces.